AFTER #[unassigned]: an Interview with James Saunders. (April 2016) - Lash, Dominic; Saunders, James
Abstract: I have long been intrigued by the way James Saunders' music is at home both in the more canonical new music contexts (such as the Darmstädter Ferienkurse, Donaueschinger Musiktage or Huddersfield Contemporary Music Festival) and in more underground, fugitive contexts. This may be because – unlike so many composers who tip the scales to one side or another – Saunders is equally interested in relationships between sounds and relationships between people. The following text explores the ways Saunders' work has balanced these interests; it originated in an interview initiated by Simon Reynell to accompany the CD release of Saunders' composition assigned #15, performed by Apartment House, on Reynell's Another Timbre label. We subsequently followed up with a second interview extending the discussion to more recent work.